1988
DOI: 10.1590/s0102-311x1988000300003
|View full text |Cite
|
Sign up to set email alerts
|

Sorologia de malária vivax no foco Aldeia dos Índios, município de Peruíbe, Estado de São Paulo, 1984 a 1986

Abstract: Registraram-se, nos últimos vinte anos, casos autóctones de malária por Plasmodium vivax no Município de Peruíbe (24,19ºS e 47,00ºW), Litoral Sul do Estado de São Paulo, com presença de portadores assintomáticos ou oligossintomáticos associada ou não a parasitemias subpatentes. O problema na área é também conhecido como "bromélia-malária"; os vetores pertencem ao subgênero Kerteszia: Anopheles (K.) cruzii e A. (K.) bellator. A partir do segundo semestre de 1984 foram realizados, semestralmente, inquéritos soro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 4 publications
0
19
0
5
Order By: Relevance
“…cruzii / A. homunculus specimens were found infected by P. falciparum (data not shown) in this study and it was surprising, as bromeliad malaria has traditionally been related to P. vivax infections (Carvalho et al 1988. The fact that these specimens were not captured in the CDC-CO 2 traps in the canopy means that the relationship between P. falciparum and simian malaria is less clear-cut.…”
Section: A Cruzii/a Homunculusmentioning
confidence: 62%
See 1 more Smart Citation
“…cruzii / A. homunculus specimens were found infected by P. falciparum (data not shown) in this study and it was surprising, as bromeliad malaria has traditionally been related to P. vivax infections (Carvalho et al 1988. The fact that these specimens were not captured in the CDC-CO 2 traps in the canopy means that the relationship between P. falciparum and simian malaria is less clear-cut.…”
Section: A Cruzii/a Homunculusmentioning
confidence: 62%
“…Anopheles cruzii is still involved in human and simian malaria transmission in valleys in the Atlantic Forest in the states of São Paulo and Santa Catarina (Carvalho et al 1988, Branquinho et al 1997, and when tested by ELISA were found to be infected with P. vivax and one of its variants, P. vivax VK247 (Branquinho et al 1997).…”
Section: A Cruzii/a Homunculusmentioning
confidence: 99%
“…Currently An. cruzii is involved in the maintenance of several species of human and simian malaria that occurs in the valleys of the Atlantic Coastal Rain Forest in both states Rio de Janeiro and São Paulo (Carvalho et al 1988, Azevedo 1997, Branquinho et al 1997. In addition, this species is a vector of the simian malarias in Brazil (Deane 1986).…”
Section: Malaria Vectors In Brazil Belong To the Nyssorhynchus And Kementioning
confidence: 99%
“…However every year there are a few autochtonous cases, diagnosed as being due to Plasmodium vivax, some of them with atypical, very mild and transitory clinical symptoms. These present low parasitaemia, of very short duration, frequently clearing even before a treatment can be initiated (Carvalho et al 1988). These malaria cases are generally concentrated in a few foci, part of them located in the Vale do Ribeira and at the Serra do Mar (Carvalho et al 1988, SUCEN 1990.…”
mentioning
confidence: 99%